Dose-Blinded Myosin Inhibition in Patients With Obstructive Hypertrophic Cardiomyopathy Referred for Septal Reduction Therapy: Outcomes Through 32 Weeks. Issue 11 (6th November 2022) - Desai, Milind Y.; Owens, Anjali; Geske, Jeffrey B.; Wolski, Kathy; Saberi, Sara; Wang, Andrew; Sherrid, Mark; Cremer, Paul C.; Naidu, Srihari S.; Smedira, Nicholas G.; Schaff, Hartzell; McErlean, Ellen; et al.
Abstract : Background: Septal reduction therapy (SRT) in patients with intractable symptoms from obstructive hypertrophic cardiomyopathy (oHCM) is associated with variable morbidity and mortality. The VALOR-HCM trial (A Study to Evaluate Mavacamten in Adults with Symptomatic Obstructive Hypertrophic Cardiomyopathy Who Are Eligible for Septal Reduction Therapy) examined the effect of mavacamten on the need for SRT through week 32 in oHCM. Methods: A double-blind randomized placebo-controlled multicenter trial at 19 US sites included patients with oHCM on maximal tolerated medical therapy referred for SRT with left ventricular outflow tract gradient ≥50 mm Hg at rest or provocation (enrollment, July 2020–October 2021). The group initially randomized to mavacamten continued the drug for 32 weeks, and the placebo group crossed over to dose-blinded mavacamten from week 16 to week 32. Dose titrations were based on investigator-blinded echocardiographic assessment of left ventricular outflow tract gradient and left ventricular ejection fraction. The principal end point was the proportion of patients proceeding with SRT or remaining guideline eligible at 32 weeks in both treatment groups. Results: From the 112 randomized patients with oHCM, 108 (mean age, 60.3 years; 50% men; 94% in New York Heart Association class III/IV) qualified for week 32 evaluation (56 in the original mavacamten group and 52 in the placebo cross-over group). After 32 weeks, 6 of 56 patients (10.7%) in the original mavacamten group and 7 of 52 patients (13.5%) in the placebo cross-over group met SRT guideline criteria or elected to undergo SRT. After 32 weeks, a sustained reduction in resting left ventricular outflow tract gradient (−33.0 mm Hg [95% CI, −41.1 to −24.9]) and Valsalva left ventricular outflow tract gradient (−43.0 mm Hg [95% CI, −52.1 to −33.9]) was observed in the original mavacamten group. A similar reduction in resting (−33.7 mm Hg [95% CI, −42.2 to −25.2]) and Valsalva (−52.9 mm Hg [95% CI, −63.2 to −42.6]) gradients was quantified in the cross-over group after 16 weeks of mavacamten. After 32 weeks, improvement by ≥1 New York Heart Association class was observed in 48 of 53 patients (90.6%) in the original mavacamten group and 35 of 50 patients (70%) after 16 weeks in the cross-over group. Conclusions: In severely symptomatic patients with oHCM, 32 weeks of mavacamten treatment showed sustained reduction in the proportion proceeding to SRT or remaining guideline eligible, with similar effects observed in patients who crossed over from placebo after 16 weeks. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04349072.